Perbedaan Kadar Vitamin D3 pada Penderita Tuberkulosis Paru Sebelum dan Sesudah Satu Bulan Terapi Obat Anti Tuberkulosis - Kuncara, Rachmad Bayu; Najiah, Dewina Zumrotin (Poltekkes Kemenkes Semarang, 2024)
Pulmonary tuberculosis is an infectious disease caused by infection with the bacteria Mycobacterium tuberculosis. Patients diagnosed with pulmonary tuberculosis will receive Anti-Tuberculosis Drug (OAT) therapy for six months. In the first two months or what is called the intensive phase, the patient will be given a combination of OAT in the form of rifampicin, isoniazid, ethambutol and pyrazinamide. Several types of anti-tuberculosis drugs have the potential to affect vitamin D3 metabolism, either by interfering with absorption, metabolism or changing the action of vitamin D3. The long-term treatment process for pulmonary tuberculosis also results in a decrease in vitamin D3 levels in the blood. This study aims to determine the difference in vitamin D3 levels in pulmonary tuberculosis sufferers before and after one month of anti-tuberculosis drug therapy. This type of research is descriptive observational with a prospective cohort design without comparison. The total sample was 16 newly diagnosed pulmonary tuberculosis sufferers at the Bangetayu, Kedungmundu and Tlogosari Wetan Health Centers, Semarang City. Vitamin D3 levels in serum samples were examined using the ELISA method. The mean vitamin D3 level before OAT therapy was 19.00 ± 10.45 ng/mL, the level decreased after OAT therapy, namely 18.51 ± 4.74 ng/mL. These results indicate that administration of anti-tuberculosis drugs may have an effect on vitamin levels.